Solvothermal-Based Lignin Fractionation From Corn Stover: Process Optimization and Product Characteristics - Khongchamnan, Punjarat; Wanmolee, Wanwitoo; Laosiripojana, Navadol; Champreda, Verawat; Suriyachai, Nopparat; Kreetachat, Torpong; Sakulthaew, Chainarong; Chokejaroenrat, Chanat; Imman, Saksit (Frontiers in Chemistry, 2021)
Fractionation of lignocellulosic is a fundamental step in the production of value-added biobased products. This work proposes an initiative to extract lignin efficiently from the corn stover using single-step solvothermal fractionation in the presence of an acid promoter (H2SO4). The organic solvent used consists of ethyl acetate, ethanol, and water at a ratio of 30: 25:45 (v/v), respectively. H2SO4 was utilized as a promoter to improve the performance and selectivity of lignin removal from the solid phase and to enhance the amount of recovered lignin in the organic phase. The optimal conditions based on response surface methodology (RSM) are processing at 180°C for 49.1 min at an H2SO4 concentration of 0.08 M. The optimal conditions show an efficient reaction with 98.0% cellulose yield and 75.0% lignin removal corresponding to 72.9% lignin recovery. In addition, the extracted lignin fractions, chemical composition and structural features were investigated using fourier transform infrared spectrophotometer (FTIR), thermogravimetric analysis (TGA), elemental analysis, and 13C nuclear magnetic resonance methods (13C-NMR). The results indicate the recovered lignin is primarily cross-linked by the β-O-4 linkages. The existence of H2SO4 promotes the cleavage of the intramolecular β–aryl structures at β-O-4, β-β, and β-5 linkages. The catalyst supported the hydrogenation of the Cβ–Hβ bonds associated with the side chain’s signal in the β-O-4/α-O-4 linkage, which is attributed to guaiacyl linked with the p -hydroxyphenyl units (G/H). The potential cleavage mechanism to degrade lignin-derived oligomers is proposed and discussed.